Fostering Village Governance: Formulating Regulations on Village-Owned Enterprises in Pabuaran Village, Serang Regency - Pipih Ludia Karsa; H. Ade Marpudin (Probono and Community Service Journal, 2022)
To fulfill national priorities, especially "promoting the general welfare," as stated in the Preamble of the Republic of Indonesia Constitution of 1945. Villages are essential in national development efforts because most Indonesians live in rural regions. Hence, attempts to promote national stability through community economic recovery are necessary. Through the creation of BUMDesa, it is deemed essential for each community to develop its potential. By developing BUMDesa and/or optimizing BUMDesa that has already been formed, it is vital to pay attention to the commercial operations that will be carried out as a driving force for village administration and as a support for the village community's economy. Including Pabuara Village in the Pabuaran District of Serang Regency, which in this instance, serves as the university's foster village. Creating BUMDesa necessitates the creation of a legal foundation, specifically the Village Regulations, to facilitate commercial operations (Perdes)